Assessment of Nurses Beliefs Toward Reporting of Suspected child abuse in Jordan) - Al-Shannaq, sami; Mohammed, saja (Iraqi National Journal of Nursing Specialties, 2005)
Abstract Objective: To assess nurses’ beliefs toward reporting suspected child abuse. To achieve the objectives of the study a questionnaire of child abuse was used. Methodology:- The sample of the study consist of (224) registered nurses who were employed in general hospitals, pediatric hospitals, National psychiatry and mental illness center, nursing colleges, nursing schools. Data were collected from 20 April 2004 to 20 June 2004.Data were analyzed through the application of descriptive statistical analysis. Percentage frequency and mean and inferential data analysis ANOVA. Results: - The result of the study revealed that there was highly significant positive relationship between education and time spent with children, and significant relationship between nurses’ beliefs and reporting behavior of suspected child abuse. It was concluded from the study that the nurses had poor knowledge of reporting procedure regard suspected child abuse. Recommendation: - The study recommended improving nurses’ skills in reporting of suspected child abuse as importance of nurse’s education and training about child abuse and reporting procedure of suspected child abuse